Актуарні розрахунки – основа забезпечення фінансової стійкості страхової компанії - Гнатенко, Олена Андріївна (My University, 2011)
Розглянуто історичні передумови виникнення актурних розрахунків, їх особливості розвитку на ринку страховиг послуг в Україні. Висвітлено основні проблемні питання актуарної справи в Україні. Запропоновано створити національну систему підготовки і сертифікації актуаріїв України, що відповідатиме по якості міжнародним вимогам. Historical pre-conditions of origin of actuarial calculations, their feature of development at the market of insurance services are considered in Ukraine. The basic problem questions of actuaries of Ukraine are reflected and it is suggested to build the national system of preparation and certification of actuaries of Ukraine which will answer international requirements for qualities.
Keywords: страхова компанія; страховв послуги; insurance company; insurance favour; кафедра фінансів